Effects of antifungal stewardship using therapeutic drug monitoring in voriconazole therapy on the prevention and control of hepatotoxicity and visual symptoms: A multicentre study conducted in Japan. Issue 8 (25th June 2020) - Hamada, Yukihiro; Ueda, Takashi; Miyazaki, Yoshitsugu; Nakajima, Kazuhiko; Fukunaga, Keiko; Miyazaki, Taiga; Nakada‐Motokawa, Nana; Nagao, Miki; Kawamura, Hideki; Shigemi, Akari; Ebihara, Fumiya; Kimura, Toshimi; et al.
Summary: Background: Hepatotoxicity and visual symptoms are common adverse effects (AEs) of voriconazole therapy. Objective: To retrospectively evaluate the effects of treatment modification based on therapeutic drug monitoring on AEs in patients undergoing voriconazole therapy. Methods: The target voriconazole trough concentration ( C min ) was 1‐5 µg/mL. Receiver operating characteristic curves were used to determine C min cut‐offs for AEs. Results: A total of 401 patients were included. Among 108 patients with high initial C min, voriconazole was discontinued in 32 and the dose was reduced in 71. Among 44 patients with low initial C min, voriconazole was discontinued in 4 and the dose was increased in 19. Hepatotoxicity occurred in 6.0% of patients, after a median of 10 days. Visual symptoms were evident in 9.5% of patients after a median of 4 days. Initial C min was significantly associated with visual symptoms but not hepatotoxicity, which suggested the effect of treatment modification on hepatotoxicity. However, both hepatotoxicity and visual symptoms were significantly correlated with C min at the onset of AEs, and the C min cut‐offs were 3.5 μg/mL for hepatotoxicity and 4.2 μg/mL for visual symptoms. Voriconazole was discontinued after the occurrence of AEs in 62.5% of patients with hepatotoxicity but only 26.3% of patients with visual symptoms. With dose adjustment, treatment was completed in 8/9 patients with hepatotoxicity and 27/28 patients with visual symptoms. Conclusions: A significant preventive effect was demonstrated on hepatotoxicity, but not on visual symptoms because of earlier occurrence. With treatment modification after the occurrence of AEs, most patients completed therapy.